From Lecture Theaters to Online Classrooms: Examining The Growth of the Flipped Classroom - Ouariach Soufiane; Ouariach Fatima Zahra; Khaldi Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Traditional models of education involve teachers imparting knowledge to students in a classroom setting. However, new learning theories suggest that students do not all acquire information in the same way. Some learn better through independent exploration and discovery, while others thrive in social environments with hands-on instruction. This debate around student-centered versus teacher-centered pedagogy is far from resolved. One approach that is gaining attention is the